Conceptualizing post intensive care syndrome in children: the PICS-p Framework* - Manning, Joseph C.; Pinto, Neethi P.; Rennick, Janet E.; Colville, Gillian; Curley, Martha A.Q. (Lippincott, Williams & Wilkins, 2018)
Context: Over the past several decades, advances in pediatric critical care have saved many lives. As such, contemporary care has broadened its focus to also include minimizing morbidity. Post Intensive Care Syndrome, also known as “PICS,” is a group of cognitive, physical, and mental health impairments that commonly occur in patients after ICU discharge. Post Intensive Care Syndrome has been well-conceptualized in the adult population but not in children.